2021
DOI: 10.1007/s13201-021-01536-9
|View full text |Cite
|
Sign up to set email alerts
|

Fulvic acid isolation and characterisation from water of a Ramsar Lake Mansar, J&K, India

Abstract: The present study was undertaken with the aim to understand the chemical properties of aquatic fulvic acid in a clear water Lake Mansar. Along with that, the physical and chemical environment of the lake was also analysed. Fulvic acid was isolated from the water of Lake Mansar following IHSS recommended methodology and was subjected to characterisation, viz. elemental analysis, H-NMR and FTIR spectroscopy. The yield of fulvic acid from water of Lake Mansar was 0.22 mg/L that was far less than coloured aquatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It was also observed that slow increase in the percentage of removal occurs due to the large concentration of hydrogen ions in the solution, which occupy the active sites when the pH falls within the range of 1 to 4. At higher pH range from 4 to 7, ACSL surface gain negatively charges on higher pH due to this reason possibility increases the more attraction between the cationic dye and ACSL along with the electrostatic forces of attraction than RSL surfaces [20,23,37]. Due to the occupation of the active sites by hydrogen ions, both adsorbents (RSL and ACSL) repels the BG dye cations ions, leading to the lower adsorption.…”
Section: Effect Of Ph Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also observed that slow increase in the percentage of removal occurs due to the large concentration of hydrogen ions in the solution, which occupy the active sites when the pH falls within the range of 1 to 4. At higher pH range from 4 to 7, ACSL surface gain negatively charges on higher pH due to this reason possibility increases the more attraction between the cationic dye and ACSL along with the electrostatic forces of attraction than RSL surfaces [20,23,37]. Due to the occupation of the active sites by hydrogen ions, both adsorbents (RSL and ACSL) repels the BG dye cations ions, leading to the lower adsorption.…”
Section: Effect Of Ph Solutionmentioning
confidence: 99%
“…Various types of adsorbents such as natural, agricultural, industrial wastes and their prepared activated adsorbent in adsorption process are more attractive due to their easy availability, low-cost or no cost and minimum sludge production [19]. Previously researchers reported different type of low cost adsorbents and activated adsorbents such Assalix alba leaves [20], chemically modified areca nut husk [21], chemically activated date pit carbon [22], activated carbon prepared from waste banana peels [23], activated carbon derived from medlar seeds [24], activated carbon [25], Giombo persimmon seed [26], activated carbon prepared from flamboyant pod, eucalyptus tree, coconut shell and corn cob [27] and nanohydroxyapatite/chitosan composite [28] for removal of brilliant green dye from wastewater.…”
Section: Introductionmentioning
confidence: 99%